Surgical treatment of Hallux Rigidus – arthrodesis or resection arthroplasty? Retrospective observational study - Dovydas Rapolis; Matas Urmanavičius; Aleksas Makulavičius; Valentinas Uvarovas (Lietuvos Chirurgija)
Introduction. Hallux Rigidus, a degenerative disease of the first metatarsophalangeal joint (MTP), causes pain during movement, reduces joint mobility, and impairs quality of life. Conservative treatment methods are effective only in the early stages of the disease, and surgical treatment is usually recommended for advanced pathology. Arthrodesis procedure is the gold standard. This surgery effectively and relatively quickly reduces painful symptoms but sacrifices joint mobility. An alternative is resection arthroplasty. There is no consensus in the literature regarding the long-term outcomes of these two treatment methods. The aim of this study is to determine which method is superior in improving patients’ quality of life and foot function. Methods. A retrospective observational study was conducted on 41 patients who were followed up for 2–4 years after surgery. Of these, 20 underwent resection arthroplasty, 21 – arthrodesis. Patients’ quality of life and subjective foot function were assessed using two standardized questionnaires: SEFAS and Short Form-12. Additional questions on patient satisfaction with the surgery were also evaluated. Results. Patient satisfaction with the surgery was high in both groups (80%). There were no statistically significant differences in patients’ ankle and foot function assessed by SEFAS scale and psychological quality of life assessed by SF 12 (Mental Score): p = 0.14 and p = 0.729, respectively. Patients rated their physical quality of life significantly better, assessed by SF 12 (Physical Score), after undergoing arthroplasty (p = 0.02), and foot function recovered approximately 1 month faster compared to arthrodesis (p = 0.006). There were no cases of revision surgery, infectious complications, or non-unions in either group. Conclusions. Both surgical techniques are effective and improve patients’ functional status, but subjective foot function is better in the early postoperative period after resection arthroplasty. The majority of patients in both groups would recommend the surgery under similar circumstances.